YOUTH: PROBLEMS AND APPROACHES (Editor: S. J. Shamsie, M.D.) - Levinson, M.D., Edward D. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1974)
S. J. Shamsie, M.D., ed. YOUTH: PROBLEMS AND APPROACHES. Toronto: The Macmillan Company, 1973. 384 pp. $8.75.